The Effect of Compaction Towards Resistivity Value - Abd Malik, Ahmad Khairul; MADUN, AZIMAN; Hazam Rizal, Amirul Haziq (Journal of Sustainable Underground Exploration, 2022)
Electrical resistivity tomography is a non-destructive method of site investigation that involves injecting electricity into the sample and measuring subsurface resistance. This study looked at the effects of compaction on soil as well as the relationship between different degrees of compaction of soil and resistivity value. The soil used in this experiment was lateritic soil. The sample was compacted in a standard proctor mould with a diameter of 10.20cm and 11.6 cm height. The soil’s resistivity was measured after the soil was compacted inside the mould. The resistivity testing was conducted using soil resistivity meter model Miller 400A. ASTM G57 was used for electrical resistivity testing. This research emphasizes the impact of compaction on resistivity value, as soil reduces resistivity value when the soil has higher moisture content which is 120 ?m at 37%, and 190 ?m at 25%. By comparing the results of different moisture content of soil samples under varied degrees of compaction, better resistivity interpretation tables may be generated.